Computational method for shaping the vibro-isolation properties of semi-active and active systems - Krzyżyński, T.; Maciejewski, I. (Archives of Mechanics, 2019)
The paper deals with an original methodology for modelling and control system design of the semi-active and active systems. At first a generalised simulation model of the vibration reduction system is formulated in such a way that it represents the dynamics of human body exposed to mechanical vibration. Then a novel control system design is proposed in order to adjust force characteristics of the fundamental elements included in the suspension system and consequently to reduce the harmful effects of vibration. Finally, a computational method is experimentally verified by selecting the vibro-isolation properties of an exemplary horizontal seat suspension for a specific input vibration.